Cytosolic estrogen and progesterone receptor content in the endometriotic tissues and endometrium in women with and without endometriosis (Medical Journal of Indonesia, 2005)
In order to have a profile of cytosolic estrogen and progesterone receptors in either endometriotic tissue or endometrium in patients with and without endometriosis a cross-sectional study was performed involving 43 infertile women. They consisted of 31 (72.09%) endometriosis and 12 (27.91%) non-endometriosis cases; their average age was 32 ±4 years and 32 ±3 years respectively, with the average length of menstrual cycle 31 ±8 days and 29 ±1 days respectively. The endometriotic tissue was obtained by excision during ope-rative laparoscopy procedure, while the endometrium was obtained by biopsy following hysteroscopy procedure. These procedures were conducted within the periovulatory period (on Day 13-18 of the cycle).The sex steroid receptor content in the cytosol was measured quantitatively using enzyme-immunoassaymethod, and calculated as sex steroid receptor/cytosol protein (fmol/ml cytosol). It was found that the average cytosolic estrogen receptor concentration in the respective tissues were 512.99fmol/ml in the endometriotic ovary compared with 2369.17 in normal ovary and 632.18 fmol/ml in the endometriotic peritoneum compared with 9607.61 fmol/ml in normal peritoneum;while 99.28 fmol/ml and 608.33fmol/ml in the endometrium of women with endometriosis and those without endometriosis respectively. The average cytosolic progesterone receptor concentration found in the respective tissues were 50.64fmol/ml in the endometriotic ovary compared with 6469.42 fmol/ml in normal ovary and1631.40 fmol/ml in endometriotic peritoneum compared with 12466.99 in normal peritoneum, while21.26 fmol/ml and 599.61fmol/ml in the endometrium of women with endometriosis and those without endometriosis respectively. There is no significant difference in the receptor concentration between each tissue according to its topographic origin. However, this result may assume that the responsivity on hormonal treatment in endometriosis cases willdepend on the cytosolic sex steroid receptor content in the sick tissues, and the peritoneal lesions will possibly give better response than those in other sites. A further clinical trial is necessary. (Med J Indones 2005; 14: 133-41)